2018
DOI: 10.1002/jcph.1294
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Maternal and Neonatal Pharmacokinetic Behavior of Ceftazidime

Abstract: Ceftazidime is a parenteral cephalosporin frequently used in pregnant women for treatment of urinary tract or intrauterine infections. Despite its regular use in pregnant women, ceftazidime disposition in both mother and fetus is not well understood, and a pharmacokinetic (PK) model that allows characterization and simulation of both maternal and preterm neonatal ceftazidime disposition is not available. In this study, 10 pregnant women with suspected or proven intrauterine infections in the late second and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The simulated mean plasma concentration–time profile after both single and multiple dose administration of 1 g of ceftazidime in pregnant women in their third trimester were compared with the mean clinical data published by Dallmann et al 14 . The mean concentrations are in general within the simulated 5th and 95th percentile interval (Figure 2b).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The simulated mean plasma concentration–time profile after both single and multiple dose administration of 1 g of ceftazidime in pregnant women in their third trimester were compared with the mean clinical data published by Dallmann et al 14 . The mean concentrations are in general within the simulated 5th and 95th percentile interval (Figure 2b).…”
Section: Resultsmentioning
confidence: 86%
“…The simulated mean plasma concentration-time profile after both single and multiple dose administration of 1 g of ceftazidime in pregnant women in their third trimester were compared with the mean clinical data published by Dallmann et al 14 The mean concentrations are in general within the simulated 5th and 95th percentile interval (Figure 2b). Simulations show a predicted 27% decrease in AUC in the third trimester of pregnancy, which is similar to the decrease in observed steady-state concentration reported in the literature 13 (Table 2).…”
Section: S131mentioning
confidence: 94%
“…The slight underprediction of ceftazidime exposure in the simulated subjects compared with Dallmann’s study [ 43 ] is probably because the observations stemmed from pregnant subjects under mechanical ventilation. A previous study found that mechanical ventilation decreases ceftazidime renal clearance and increases its volume of distribution [ 49 ].…”
Section: Discussionmentioning
confidence: 90%
“…As perinatal medicine is undergoing a fundamental change transforming towards a modern data-driven patient-oriented approach new tools that will predict the dynamics of biomarkers for an individual fetus or newborn will become increasingly important in maternal, neonatal and perinatal care. We developed PMX-based algorithms to optimize and individualize dosing of therapeutics in the field of perinatal medicine ( Wilbaux et al, 2016a ; Wilbaux et al, 2016b ; Koch et al, 2017 ; Nekka et al, 2017 ; van Donge et al, 2018 ; Dallmann et al, 2019 ; van Donge et al, 2019 ; Wilbaux et al, 2019 ; van Donge et al, 2020a ; van Donge et al, 2020b ; Koch et al, 2020c ; Dao et al, 2020 ; Samiee-Zafarghandy et al, 2022 ). It is time to go beyond classical pharmacological applications and develop algorithms condensing the wealth of clinical data and physiology knowledge into predictive tools coping with the dynamics of biomarkers for an individual fetus or neonate.…”
Section: Discussionmentioning
confidence: 99%